Dendrobine Inhibits γ-Irradiation-Induced Cancer Cell Migration, Invasion and Metastasis in Non-Small Cell Lung Cancer Cells - Ye-Ram Kim; Ah-Reum Han; Jin-Baek Kim; Chan-Hun Jung (Biomedicines, 2021)
The use of ionizing radiation (IR) during radiotherapy can induce malignant effects, such as metastasis, which contribute to poor prognoses in lung cancer patients. Here, we explored the ability of dendrobine, a plant-derived alkaloid from Dendrobium nobile, to improve the efficacy of radiotherapy in non-small cell lung cancer (NSCLC). We employed Western blotting, quantitative real-time (qRT)-PCR, transwell migration assays, and wound-healing assays to determine the effects of dendrobine on the migration and invasion of A549 lung cancer cells in vitro. Dendrobine (5 mm) inhibited γ-irradiation-induced migration and invasion of A549 cells by suppressing sulfatase2 (SULF2) expression, thus inhibiting IR-induced signaling. To investigate the inhibitory effects of dendrobine in vivo, we established a mouse model of IR-induced metastasis by injecting BALB/c nude mice with γ-irradiated A549 cells via the tail vein. As expected, injection with γ-irradiated cells increased the number of pulmonary metastatic nodules in mice (0 Gy/DPBS, 9.8 ± 1.77; 2 Gy/DPBS, 20.87 ± 1.42), which was significantly reduced with dendrobine treatment (2 Gy/Dendrobine, 10.87 ± 0.71), by prevention of IR-induced signaling. Together, these findings demonstrate that dendrobine exerts inhibitory effects against γ-irradiation-induced invasion and metastasis in NSCLC cells in vitro and in vivo at non cytotoxic concentrations. Thus, dendrobine could serve as a therapeutic enhancer to overcome the malignant effects of radiation therapy in patients with NSCLC.